Prevalence of systemic anticancer therapy for patients within the last 30 days of life: experience in a private hospital oncology group. Issue 3 (March 2017) - Wein, L.; Rowe, C.; Brady, B.; Handolias, D.; Lipton, L.; Pook, D.; Stanley, R.; Haines, I.
Abstract : Background: In recent years, there has been a significant increase in the number of cancer treatments that have become available. However, it has remained difficult to choose the most appropriate time to cease active therapy in individual patients. Aims: To determine the proportion of patients being treated with palliative intent who received systemic anticancer treatment in the last 30 days of life. Methods: This is a retrospective cohort study conducted within the Melbourne Oncology Group at Cabrini Hospital. Patients managed with palliative intent who died between 1 January 2014 and 30 June 2014 were included. Outcomes measured were the percentage of patients who received systemic anticancer treatment in the last 30 days of life, palliative care referral status, Emergency Department presentations, hospital admissions and place of death. Results: A total of 80 patients was included in the study. Of these patients, 21 (26%) received systemic anticancer treatment in the last 30 days of life. There was no statistically significant difference between patients who received treatment in the last month of life and those who did not in terms of the number of patients who were referred to palliative care, presented to an Emergency Department, were admitted to hospital or died in an acute ward. Conclusion: Although over a quarter of patients dying from advanced cancer received anticancer treatment in the last month of life, these patients did not present acutely to hospital more often and had the same extent of palliative care team involvement.